10.65133 ANALISIS EKONOMI BERKELANJUTAN DAN INKLUSIF TERHADAP REALISASI KPR SUBSIDI FLPP DI KEPULAUAN BANGKA BELITUNG - Ramadhan; Rizal R. Manullang; Hendarti Tri Setyo Mulyani (Jurnal Ilmiah Niaga Bisnis Elektronik, 2025)
Abstract - This study investigates the influence of sustainable and inclusive economic factors on the realization of subsidized housing loans (KPR FLPP) in Bangka Belitung Islands, Indonesia, during 2022–2024. Despite the region facing economic slowdown, rising unemployment, and environmental degradation, KPR FLPP realization remained unexpectedly high, prompting further analysis. This study aims to examine the impact of economic growth (PDRB ADHK), beneficiary income, and open unemployment rate on KPR FLPP realization, and the moderating role of Environmental Quality Index (IKLH). Using a quantitative approach and secondary data from relevant agencies, multiple linear regression and moderated regression analysis were employed. The findings reveal that economic growth and income significantly influence KPR FLPP realization, while the unemployment rate shows no significant effect. Moreover, IKLH significantly moderates the effect of economic growth and income, strengthening their relationship with housing loan realization. These results underscore the importance of environmental quality and inclusive economic policies in supporting national housing programs, particularly in regions with complex economic and ecological conditions.